2021
DOI: 10.3390/cells10020379
|View full text |Cite
|
Sign up to set email alerts
|

Human Placenta Buffers the Fetus from Adverse Effects of Perceived Maternal Stress

Abstract: Maternal stress during pregnancy is linked to several negative birth outcomes. The placenta, a unique pregnancy-specific organ, not only nourishes and protects the fetus but is also the major source of progesterone and estrogens. As the placenta becomes the primary source of maternal progesterone (P4) and estradiol between 6–9 weeks of gestation, and these hormones are critical for maintaining pregnancy, maternal stress may modulate levels of these steroids to impact birth outcomes. The objective was to test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…We found placental P4 was 15-fold higher than cortisone in ordinary pregnant women and 5.88-fold in CB. Similarly, Vuppaladhadiam’s group also reported that placental P4 was ~13-fold higher than cortisone levels ( 10 ). These results support the theory that the placenta is the primary source of P4 during pregnancy ( 11 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found placental P4 was 15-fold higher than cortisone in ordinary pregnant women and 5.88-fold in CB. Similarly, Vuppaladhadiam’s group also reported that placental P4 was ~13-fold higher than cortisone levels ( 10 ). These results support the theory that the placenta is the primary source of P4 during pregnancy ( 11 ).…”
Section: Discussionmentioning
confidence: 90%
“…Once the balance is broken, it will lead to adverse pregnancy and poor fetal outcomes. Vuppaladhadiam’s group ( 10 ) detected 10 types of steroid metabolites in P and CB using ultra-pure liquid chromatography (UPLC) MS, and they described a schematic of steroidogenesis in the maternal-fetal compartments. This diagram intuitively showed the synthesis, transport, and regulation of steroid hormones in the maternal-fetal interface ( Supplementary Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this measure of adversity may not have captured all stressors during pregnancy, which may conceal a legitimate association and in part explain the null findings. Lastly, emerging evidence has suggested that the human placenta may buffer the effects of maternal stress and protect the developing fetus,5 which could provide a biological explanation for apparent absent effects of maternal stress in this cohort.…”
Section: Discussionmentioning
confidence: 94%
“…A recent review of maternal prenatal stress and infant DNA methylation identified several candidate genes implicated in the maternal central stress response that may be critical in driving phenotype changes for offspring 4. However, recent evidence also suggests that perhaps the placenta may buffer the effects of the maternal stress response 5…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is frequently placental in origin, and cortisol levels in the mother are known to be partially placentally transferred to the fetus ( 19 21 ). In addition, stressors of either the mother, neonatal infection, or the birthing process itself may also cause the neonate to generate cortisol on its own ( 22 , 23 ). This suggests that the bi-directional effect within the maternal/fetal dyad on cortisol has a vital role in the maintenance of neonatal homeostasis.…”
Section: Introductionmentioning
confidence: 99%